STUDI PENGUASAAN MATEMATIKA DAN BAHASA INGGRIS MAHASISWA PROGRAM STUDI PENDIDIKAN GURU SEKOLAH DASAR (PGSD) - Pramudita, Wahyu; Anugraheni, Indri (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2017)
This research was a descriptive non-experimental (field study) that attempted to describe the level of studentsâ mastery on the primary teachers educationâs student of Atma Jaya Catholic University, specifically the cognitive aspects of basic mathematic and English language referred to curriculum of 2008. This study aimed to 1) mapping of the studentsâ mastery of mathematics and its relevancy, 2) mapping of the studentsâ mastery of English Language and its relevancy. The respondents of this study were 56 students of 2010-2012 batches. The results of this study indicated that the mathematical ability of students was considered good and the English language ability was sufficient.